Designing Circular Packaging Systems for Everyday Beverages Using Oil Palm Empty Fruit Bunch Waste - Nugroho, Handi Wilujeng; Putri, Alyani Rahma; Putra, Rama Dani Eka; Fitri, Tessa Zulenia (Journal of Advanced and Applied Science and Technology, 2025)
The rapid growth of single-use beverage packaging has intensified environmental challenges due to high material complexity, limited recyclability, and continued dependence on fossil-based resources. Conventional recycling approaches have proven insufficient to address these structural issues, particularly for multilayer plastic packaging commonly used for liquid beverages. This study proposes a circular packaging system for everyday beverage applications utilizing oil palm empty fruit bunch (EFB) waste as a renewable fiber-based raw material. Indonesia, as the world’s largest palm oil producer, generates tens of millions of tons of EFB annually, most of which remains underutilized or poorly managed. Through a system-oriented design approach, EFB is repositioned from low-value agricultural residue into a strategic material input for fiber-based beverage packaging. The research develops a conceptual circular packaging framework that integrates agricultural waste streams, fiber extraction and material engineering, packaging design, industrial compatibility, and end-of-life management within a closed-loop system. Rather than focusing on laboratory-scale material novelty, the study emphasizes system integration, value retention, and scalability using established fiber-processing technologies adapted to liquid packaging requirements. Comparative assessment indicates that EFB-based packaging offers significant advantages over conventional multilayer plastics in terms of material circularity, recyclability, carbon footprint reduction, and alignment with circular economy principles. The findings demonstrate that EFB-based circular packaging systems are technically feasible, industrially adaptable, and environmentally advantageous for everyday beverage applications. The primary contribution of this research lies in the development of a system-level circular packaging design model that simultaneously addresses agricultural waste management and packaging sustainability, offering a scalable pathway toward more resilient and circular production-consumption systems.